2016
DOI: 10.3389/fpls.2016.00063
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Rutin and Quercetin Biosynthesis through Flavonoids-Related Gene Expression in Fagopyrum tataricum Gaertn. Hairy Root Cultures with UV-B Irradiation

Abstract: Transformed hairy roots had been efficiently induced from the seedlings of Fagopyrum tataricum Gaertn. due to the infection of Agrobacterium rhizogenes. Hairy roots were able to display active elongation with high root branching in 1/2 MS medium without growth regulators. The stable introduction of rolB and aux1 genes of A. rhizogenes WT strain 15834 into F. tataricum plants was confirmed by PCR analysis. Besides, the absence of virD gene confirmed hairy root was bacteria-free. After six different media and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 60 publications
6
41
0
Order By: Relevance
“…UNZ primarily inhibited gene expression in relation to diterpenoid biosynthesis metabolic pathways. It was evident that uniconazole could down-regulate the genes coding ent-kaurene oxidase involving in the GA3 metabolism, which were consistent with UNZ catalyzing the oxidation of ent-kaurene to ent-kaurenoic acid in gibberellin biosynthesis (Izumi, Kamiya, Sakyrai, Oahio, & Takahashi 1985 (Huang et al, 2016) and this phenomenon was also observed in our study (Table 1).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…UNZ primarily inhibited gene expression in relation to diterpenoid biosynthesis metabolic pathways. It was evident that uniconazole could down-regulate the genes coding ent-kaurene oxidase involving in the GA3 metabolism, which were consistent with UNZ catalyzing the oxidation of ent-kaurene to ent-kaurenoic acid in gibberellin biosynthesis (Izumi, Kamiya, Sakyrai, Oahio, & Takahashi 1985 (Huang et al, 2016) and this phenomenon was also observed in our study (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, brassinosteroid-6-oxidase (CYP85A2) related to the synthesis of brassinosteroid was also annotated and up-regulated, which can enhance dry weight of aboveground and belowground biomass of plants (Huang et al, 2016) and this phenomenon was also observed in our study (Table 1). Red arrows indicate positive regulation, and blue arrows indicate negative regulation caffeoyl-CoA O-methyltransferase related to the synthesis of flavonol were annotated and up-regulated.…”
Section: Discussionsupporting
confidence: 79%
“…The biosynthesis of flavonoid and the expression levels of related genes are regulated by phytochrome, cryptochrome, phototropin, and UV-B photoreceptors [43,44]. For example, flavonoid biosynthesis was suppressed by increasing the amount of far-red light of phytochrom [45], whereas UV-A / blue light induction of the flavonoids biosynthesis was mediated principally by cryptochrome [44], in addition, the biosynthesis of flavonoids and the expression levels of related genes are induced most effectively by UV-B light [46,47]. In fact, a white light source that contains all these wavelengths is usually used to induce flavonoid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The root material was extracted twice in dry ice/cold methanol for 24 h at 4°C. The rutin content was analyzed by high-performance liquid chromatography (HPLC) from triplicate independent extractions for each line as described previously (Huang et al, 2016).…”
Section: Measurement Of Rutin By High-performance Liquid Chromatographymentioning
confidence: 99%